Detection of retinal changes in Parkinson’s disease with spectral-domain optical coherence tomography - Aaker, Grant D (Dove Medical Press, 2010)
PURPOSE: This pilot study investigated whether high-resolution spectral-domain optical coherence tomography (SD-OCT) could detect differences in inner retinal layer (IRL), peripapillary retinal nerve fiber layer (RNFL), and macular thickness between patients with Parkinson’s disease (PD) and controls. METHODS: Both eyes of patients with PD and age-matched controls were imaged with the Heidelberg Spectralis(®) HRA + OCT. RNFL, IRL, and macular thickness were measured for each eye using Heidelberg software. These measurements were compared with validated, published normal values for macular and RNFL thickness, and compared with matched controls for IRL thickness. RESULTS: Eighteen eyes from nine subjects with PD and 19 eyes of 16 control subjects were evaluated using SD-OCT. The average age of PD patients was 64 years with a range of 52–75 years. The average age of controls was 67 years with a range of 50–81 years. No significant reduction in IRL thickness was detected between PD patients and age-matched controls at 13 points along a 6 mm horizontal section through the fovea. No significant difference in RNFL thickness was detected between PD patients and published normal values. Overall average RNFL thickness was 97 μm for PD patients, which exactly matched the normative database value. However, significant differences in macular thickness were detected in three of nine subfields between PD subjects and published normal values. In PD subjects, the outer superior subfield was 2.8% thinner (P = 0.026), while the outer nasal and inner inferior subfields were 2.8% (P = 0.016) and 2.7% (P = 0.001) thicker compared to published normal values. CONCLUSION: In this pilot study, significant differences in macular thickness were detected in three of nine subfields by SD-OCT. However, SD-OCT did not detect significant reductions in peripapillary RNFL and IRL thickness between PD patients and controls. This suggests that macular thickness measurements by SD-OCT may potentially be used as an objective, noninvasive, and easily quantifiable in vivo biomarker in PD. Larger, longitudinal studies are needed to explore these relationships further.